2012
DOI: 10.1002/eji.201142320
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cellular immunity by antibodies against calreticulin

Abstract: Although caltreticulin (CRT) is mainly a residential ER protein, it is also expressed on the membrane surface of various types of cells exhibiting multiple functions. We report here that intraperitoneal administration of a soluble recombinant CRT fragment (rCRT/39-272) led to a substantial decrease in delayed type hypersensitivity (DTH) responses in BALB/c mice and EAE in C57BL/6 mice. In the recall response against keyhole limpet hemocyanin (KLH) in vitro, draining lymph node cells from the rCRT/39-272-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Some of the animals (4 from each group) were sacrificed on day 9 for splenocytes and the rest (6 mice per group) were scored daily for EAE severity up to 28 days. In line with our previous report (Qiu et al, 2012), i.p. administration of rCRT/39-272, but not rEGFP or PBS, mildly reduced EAE severity (Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Some of the animals (4 from each group) were sacrificed on day 9 for splenocytes and the rest (6 mice per group) were scored daily for EAE severity up to 28 days. In line with our previous report (Qiu et al, 2012), i.p. administration of rCRT/39-272, but not rEGFP or PBS, mildly reduced EAE severity (Fig.…”
Section: Resultssupporting
confidence: 91%
“…We have recently demonstrated that i.p. injection of rCRT/39-272, a potent stimulator of B cells and macrophages (Hong et al, 2010), could modulate DTH as well as EAE in mice (Qiu et al, 2012). In subsequent experiments addressing the question if EAE modulation by rCRT/39-272 was related to Th2/Th1 balance shift, groups of naïve C57BL/6 mice were s.c. immunized, on day 0, with MOG 35-55 in CFA (100 g/mouse), followed by i.p.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations